(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
This paper analyses the trade networks between Italy and the Black Sea and lower Danube regions through the study of the distribution of Italian terra sigillata in these provinces. Firstly, a bibliographical survey of the finds is provided, with an updated catalogue of stamps. Secondly, the imports of Italian pottery are compared to those of Italian amphorae, drawing parallels between the circulation of different goods in different areas of the region and analysing the relationship with the army presence and trade routes.